Sistemas de información para la gestión académica para el departamento de planeamiento de la Universidad Técnica de Cotopaxi - Guachamin Andrango, Diego Gabriel (2017)
Information systems contain a set of elements that are integrated to the process, store and distribute information in an effective and opportune way for decision making. This type of systems is not commonly used in organizations, especially in public due to the high cost involved in automating and implementing computer systems. Many companies today still maintain processes that are carried out manually, slowing down the time in information processing and reporting; For this reason the main objective of this work was to develop a system for the academic management of the Department of Planning and Institutional Development of the Cotopaxi Technical University, located in El Ejido neighborhood, San Felipe sector, Latacunga city, Cotopaxi province. For the software requirements analysis stage, the SCRUM methodology was used to streamline the software development process for product construction. This methodology is based on the analysis, design, coding and testing stages of the software. In the system development stage, the development environment of Visual Studio .NET, with RAZOR rendering engine in CSHTML web pages, was used by connecting to a database manager in Microsoft SQL Server 2012. The variables that entered the system were obtained through interviews with the administrative staff of the Department of Planning and Institutional Development. The result of the information system development process was the automation of 60 quality indicators based on seven criteria: quality in teaching, similarity in gender, student quality, complementary training, student welfare, research system and linkage system. It is concluded that given the computerization needs of the Department of Planning and Institutional Development, the implementation of this developed system will allow the processing of information corresponding to the academic management in a fast, reliable and safe way, reducing times in the delivery of reports or reports that require quality indicators.